Epigenetic mechanisms underlying the effects of triptolide and tripchlorolide on the expression of neuroligin-1 in the hippocampus of APP/PS1 transgenic mice - Xiaomei Lu; Baolin Yang; Hao Yu; Xiaoling Hu; Jing Nie; Bin Wan; Ming Zhang; Cheng Lü (Taylor & Francis Group, 2019)
Context: Neuroligin-1 (NLGN1) is a cell adhesion protein located on the excitatory postsynaptic membrane. β-Amyloid (Aβ)-induced neuroinflammation decreases NLGN1 expression through epigenetic mechanisms. Triptolide (T10) and tripchlorolide (T4) exert protective effects on synapses in Alzheimer's disease (AD) mice, but the mechanisms remain unclear. Objective: The effects of T10 and T4 on hippocampal NLGN1 expression in AD mice and the epigenetic mechanisms were assessed using chromatin immunoprecipitation and methylated DNA immunoprecipitation. Materials and methods: Sixty APP/PS1 transgenic mice were randomly divided into an AD model group, a T10-treated group and a T4-treated group (n = 20); 20 wild-type littermates served as the control group. APP/PS1 transgenic mice were intraperitoneally injected with T10 (0.1 mg/kg) and T4 (25 μg/kg) once per day for 60 days. NLGN1 expression was examined using western blotting and quantitative PCR. Results: T10 and T4 increased the levels of the NLGN1 protein and mRNA in hippocampus of AD mice. T10 and T4 inhibited the binding of HDAC2 (p< 0.01) and MeCP2 (p< 0.01 and p< 0.05, respectively) to the NLGN1 promoter, and cytosine methylation (1.2305 ± 0.1482/1.2554 ± 0.3570 vs. 1.6578 ± 0.1818, p< 0.01) at the NLGN1 promoter in the hippocampus of AD mice. T10 and T4 increased the level of acetylated histone H3 (0.7733 ± 0.1611/0.8241 ± 0.0964 vs. 0.5587 ± 0.0925, p< 0.01) at the NLGN1 promoter in the hippocampus of AD mice. Conclusions: T10 and T4 may increase hippocampal NLGN1 expression in AD mice through epigenetic mechanisms, providing a new explanation for the mechanism underlying the protective effects of T10 and T4 on synapses.